Role-play facilitates children’s mindreading of those with atypical color perception - Furumi, Fumikazu; Koyasu, Masuo (Frontiers in Psychology, 2014)
The present study examined the effects of role-play experience on children’s mindreading ability. Forty-one primary school children (20 boys, 21 girls, mean age: 9.37 years, range: 8–11 years) were introduced to a communication task in which the use of mindreading was essential. During each trial, participants viewed a shelf, presented on a laptop, which contained several familiar objects, and they were instructed to touch an object on the shelf following an order issued by a “manager” who stood at the opposite side of the shelf. There were two managers: one was a monkey manager with normal color vision, and the other was a dog manager with restricted color vision. The monkey manager could see all the objects in the same colors as the participants, whereas the dog manager saw some objects in different colors. Participants were required to respond according to the manager's instruction. In the restricted color vision condition, the dog manager saw the colors of objects differently; thus, participants had to work out his intentions, according to his different perspective. In the normal color vision condition, all objects were in the same colors as those seen by the monkey manager. Before the test phase, participants in the role-play group were provided a role-play experience in which they assumed the role of the dog manager with restricted color vision. The experimental data were analyzed using a 2 x 2 mixed-design ANOVA (role-play condition x communication partner condition) to examine differences in the error rate. Both main effects and its interaction were significant. According to the post-hoc analyses, participants in the no-role-play condition made significantly more errors in the restricted color vision condition than in the normal color vision condition, whereas no such difference was found among participants in the role-play condition. These results suggest that role-play experience could facilitate mindreading of characters with restricted color vision